Purification and Characterization of an α-Glucosidase from Rhizobium sp. (Robinia pseudoacacia L.) Strain USDA 4280 - Berthelot, Karine (American Society for Microbiology, 1999)
A novel α-glucosidase with an apparent subunit mass of 59 ± 0.5 kDa was purified from protein extracts of Rhizobium sp. strain USDA 4280, a nodulating strain of black locust (Robinia pseudoacacia L), and characterized. After purification to homogeneity (475-fold; yield, 18%) by ammonium sulfate precipitation, cation-exchange chromatography, hydrophobic chromatography, dye chromatography, and gel filtration, this enzyme had a pI of 4.75 ± 0.05. The enzyme activity was optimal at pH 6.0 to 6.5 and 35°C. The activity increased in the presence of NH(4)(+) and K(+) ions but was inhibited by Cu(2+), Ag(+), Hg(+), and Fe(2+) ions and by various phenyl, phenol, and flavonoid derivatives. Native enzyme activity was revealed by native gel electrophoresis and isoelectrofocusing-polyacrylamide gel electrophoresis with fluorescence detection in which 4-methylumbelliferyl α-glucoside was the fluorogenic substrate. The enzyme was more active with α-glucosides substituted with aromatic aglycones than with oligosaccharides. This α-glucosidase exhibited Michaelis-Menten kinetics with 4-methylumbelliferyl α-d-glucopyranoside (K(m), 0.141 μM; V(max), 6.79 μmol min(−1) mg(−1)) and with p-nitrophenyl α-d-glucopyranoside (K(m), 0.037 μM; V(max), 2.92 μmol min(−1) mg(−1)). Maltose, trehalose, and sucrose were also hydrolyzed by this enzyme.